2021
DOI: 10.1186/s13023-021-01718-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of patient access to orphan drugs in Turkey

Abstract: Background Rare diseases are life-threatening, serious, and chronic conditions that require complex care and have a low prevalence. An estimated one in 15 people worldwide are affected by rare diseases. This study aims to analyze the accessibility, reimbursement status, licensed status, and Anatomical Therapeutic Chemical (ATC) codes of drugs that the European Medicines Agency (EMA) in Turkey considers to be “orphan” pharmaceuticals. Methods The d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…This finding is consistent with a recent study examining patients' access to orphan drugs in Türkiye. In this context, access to 34 of the 105 orphan drugs on the EMA list in 2020 is still not available, and only 34 of the remaining 71 drugs are within the scope of reimbursement ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with a recent study examining patients' access to orphan drugs in Türkiye. In this context, access to 34 of the 105 orphan drugs on the EMA list in 2020 is still not available, and only 34 of the remaining 71 drugs are within the scope of reimbursement ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…It also showed that medical doctors, and those in primary care in particular, lack knowledge and experience on the diagnosis, treatment and rehabilitation of RD patients (31). Also in Turkey national policy for rare diseases and orphan drugs requires urgent updating as Turkish RD patients struggle with lack of knowledge and experience from healthcare practitioners, lack of specialist physicians and difficulties in patients' treatment and follow-up which in turn result in late or misdiagnosis, delayed access to appropriate treatment centers and inadequate number of orphan drugs (38). Finally, although awareness of RDs in many countries of Southeast Asia, including the Philippines, Singapore, Malaysia, Indonesia, Vietnam, and Thailand, is grounded on patient support and advocacy group they also suffer from insufficient number of genetic specialists, lack clinical RD expertise and possess only a few institutional centers that offer specific services to treat RDs.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, reimbursement of orphan drugs, including treatments of rare neuromuscular diseases, have varied markedly both within and across countries. Restrictions in reimbursement of orphan drugs have been reported in, for example, Central and Eastern European countries [ 71 ], Italy [ 72 ], Spain [ 73 ], and Turkey [ 74 ], as well as other settings [ 75 ]. Recently, Ward et al [ 76 ] compared reimbursement status of marketed orphan drugs in 18 European countries, as well as Canada, between January 1, 2015, and March 31, 2020.…”
Section: Patient Access To Gene Therapiesmentioning
confidence: 99%